Clinical Impact of the Immunome in Lymphoid Malignancies: The Role of Myeloid-Derived Suppressor Cells - Vetro, Calogero; Romano, Alessandra; Ancora, Flavia; Coppolino, Francesco; Brundo, Maria V.; Raccuia, Salvatore A.; Puglisi, Fabrizio; Tibullo, Daniele; La Cava, Piera; Giallongo, Cesarina; Parrinello, Nunziatina L. (Frontiers in Oncology, 2015)
The better definition of the mutual sustainment between neoplastic cells and immune system has been translated from the bench to the bedside acquiring value as prognostic factor. Additionally, it represents a promising tool for improving therapeutic strategies. In this context, myeloid-derived suppressor cells have gained a central role in tumor developing with consequent therapeutic implications. In this review, we will focus on the biological and clinical impact of the study of myeloid-derived suppressor cells in the settings of lymphoid malignancies.